London Art Worlds Mobile, Contingent, and Ephemeral Networks, 1960-1980 - Tobin, Amy, 1989-; Spencer, Catherine, 1985-; Applin, Jo (Refiguring modernism., 2018)
"Examines the rich networks of international artists and art practices that emerged in and around London during the 1960s and 1970s. Discusses diverse practices, movements, and spaces, from painting, sculpture, and film to performance, conceptual, and land art"--Provided by publisher.